The decay of the Andean Group - Sven Heldt (Intereconomics, 1977)
The creation of the Andean Group in 1969 and its ambitious program had been accompanied by optimistic expectations of its members who now have become disappointed. Regarding the conflicts within this Group the withdrawal of Chile plays a prominent part — a withdrawal which will probably have negative effects on this country, but also for the rest of the Group it represents a painful shrinkage.
Keywords: 330; Integration